Análise quaterniônica: teoremas e perspectivas em derivação e integração - REIS, Geilson Mendes dos (2015)
The study of Quaternion has been developed in the last decades and results that allow results acquaintance of the Classic Complex Analysis generalizations they could be verified for that theory. Like this, the mark of the present work is it of presenting such results besides showing new current of the previous ones, it fits to mention: new theorems in quaternionic derivation and integration.